Socio-Economic and Cognitive Impacts of Iodine Deficiency Disorders: A Systematic Literature Review with Implications for Indonesia - Rohman, Tamam Nur (Economic and Business Horizon, 2026)
Iodine deficiency disorders (IDD) remain a significant public health concern with far-reaching implications for cognitive development and socio-economic outcomes. This study aims to systematically review and synthesize existing literature on the cognitive and socio-economic impacts of iodine deficiency, with particular attention to the Indonesian context. A systematic literature review (SLR) approach was employed using databases such as Scopus, PubMed, Google Scholar, and ScienceDirect, following PRISMA-based selection procedures. A total of more than twenty relevant studies, including empirical research, systematic reviews, and global health reports, were analyzed using thematic synthesis. The findings indicate that iodine deficiency significantly impairs cognitive development, particularly during critical periods such as pregnancy and early childhood, leading to reduced intelligence quotient (IQ) and academic performance. These cognitive deficits contribute to lower educational attainment and reduced human capital, ultimately affecting economic productivity. At a global level, iodine deficiency continues to contribute to the burden of developmental intellectual disability, particularly in low socio-demographic index regions. In Indonesia, although iodized salt programs have improved iodine status, challenges remain in monitoring and equitable distribution. The study highlights the importance of universal salt iodization and integrated public health strategies to mitigate the long-term impacts of IDD.